Analysis of differential effects of host plants on the gut microbes of Rhoptroceros cyatheae - Zhang, Bingchen; Yang, Weicheng; He, Qinqin; Chen, Hangdan; Che, Bingjie; Bai, Xiaojie (Frontiers in Microbiology, 2024)
As an indispensable part of insects, intestinal symbiotic bacteria play a vital role in the growth and development of insects and their adaptability. Rhoptroceros cyatheae, the main pest of the relict plant Alsophila spinulosa, poses a serious threat to the development of the A. spinulosa population. In the present study, 16S rDNA and internal transcribed spacer highthroughput sequencing techniques were used to analyze the structure of intestinal microbes and the diversity of the insect feeding on two different plants, as well as the similarities between the intestinal microorganisms of R. cyatheae. The dominant bacteria of leaf endophytes were also compared based on the sequencing data. The results showed that Proteobacteria, Firmicutes, and Actinobacteria were the dominant phyla of intestinal bacteria, and Ascomycota was the dominant phylum of intestinal fungi.Allorhizobium-Neorhizobium-Pararhizobium-Rhizobium, Methylobacterium-Methylorubrum, and Enterococcus were the dominant genera in the intestine of R. cyatheae feeding on two plants, and the relative abundance was significantly different between the two groups. Candida was the common dominant genus of intestinal fungi in the two groups, and no significant difference was observed in its abundance between the two groups. This showed that compared with the intestinal fungi of R. cyatheae, the abundance of the intestinal bacteria was greatly affected by food. The common core microbiota between the microorganisms in A.spinulosa leaves and the insect gut indicated the presence of a microbial exchange between the two. The network correlation diagram showed that the gut microbes of R. cyatheae feeding on Gymnosphaera metteniana were more closely related to each other, which could help the host to better cope with the adverse external environment. This study provides a theoretical basis for the adaptation mechanism of R. cyatheae and a new direction for the effective prevention and control of R. cyatheae.